Kontekstualisasi Riba dalam Jual Beli Emas Online - Iis Muala Wati (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
This article aims to analyze the online gold buying and selling carried out by mini gold distributors. This research is important to study because now gold can be purchased online starting from 0.05 grams, gold has a good hedge against inflation, and there is a lack of public awareness about the practice of usury in buying and selling gold. Therefore, this legal have incident should be examined. This research is a type of qualitative research with a descriptive analysis method and a juridical-empirical approach. The data used in the form of theories related to this research, as well as interviews with national mini gold distributors. In addition, there are secondary data covering several previous studies. The results of this study indicate that the mini gold distributors are divided into three groups. First, absolutely no buying and selling of gold online. Second, buying and selling gold online with a wakalah contract, or assisted by a courier. Third, buy and sell gold online as usual. In buying and selling gold with gold, there are three conditions that must be met, namely: cash. In that instant, without delaying a moment; mutual handover at the place of sale and purchase; the size is the same, that is, it must match the same scales. However, if gold is with money, there are only two conditions, namely: cash and direct handover.